Influence of Dosage, pH, and Settling Time on the Performance of Pre-Hydrolysed Polyaluminum Chloride (PAC) in Treating Ageing Matured Leachate - Mohd Zin, Nur Shaylinda (International Journal of Integrated Engineering, 2025)
The treatment of mature leachate remains lacking due to its unique composition and characteristics, which change as the landfill ages over time. This study investigates the efficiency of the coagulation-flocculation process using Polyaluminium Chloride (PAC) to remove colour and ammoniacal nitrogen (AN) from raw matured leachate. Also, it compares the optimum removal efficiency with previous studies conducted on the same landfill leachate using PAC but in a different year. Several key parameters were evaluated, including PAC dosage (500–3000 mg/L), pH (4–9), and settling time (10–60 minutes). At the optimised designed condition of PAC dosage of 2500 mg/L, pH 6, and a 30-minute settling time, colour and AN were removed remarkably at 82% and 18% AN, respectively. These findings demonstrate significant changes in colour removal compared to previous studies, which only achieved 50–70%. While AN removal was slightly lower at 18%, the superior colour removal performance highlights the potential and relevance of this approach for treating the raw matured leachate as landfills continue to age. Thus, this study emphasised the relevance of this method for continued use in mature leachate treatment.